Influence of Bath Composition on the Electrodeposited \(\text{Co-Ni-P}\) Nanowires - Thiem, Luu Van; Tu, Le Tuan; Thang, Pham Duc (Communications in Physics, 2014)
CoNiP nanowire arrays were fabricated by electrodeposition method into polycarbonate (PC) templates at different pH values. It is obvious that the crystal structure of the CoNiP nanowires depends on the pH values of electrolyte. The XRD results show that crystal structure of the CoNiP nanowires is hcp structure and the intensity of the hcp (002) increased enhances as solution pH =5. Magnetic measurements indicate a dependence of the squareness and the coercivity of the magnetization hysteresis loop on pH values with a maximum coercivity of 1425 Oe. The morphological properties of CoNiP nanowires were studied by transmission electron microscopy (TEM). The chemical composition was determined by examination of the energy dispersive X-ray (EDS) spectra and the magnetic properties were measured by vibrating sample magnetometry (VSM).